Leveling Up the Access to Radiation Therapy in Latin America: Economic Analysis of Investment, Equity, and Inclusion Opportunities Up to 2030 - Sarria, GR (2023)
Purpose: Latin America faces a shortage in radiation therapy (RT) units and qualified personnel for timely and high-quality treatment of patients with cancer. Investing in equitable and inclusive access to RT over the next decade would prevent thousands of deaths. Measuring the investment gap and payoff is necessary for stakeholder discussions and capacity planning efforts. Methods and Materials: Data were collected from the International Atomic Energy Agency's Directory of Radiotherapy Centers, industry stakeholders, and individual surveys sent to national scientific societies. Nationwide data on available devices and personnel were compiled. The 10 most common cancers in 2020 with RT indication and their respective incidence rates were considered for gap calculations. The gross 2-year financial return on investment was calculated based on an average monthly salary across Latin America. A 10-year cost projection was calculated according to the estimated population dynamics for the period until 2030. Results: Eleven countries were included in the study, accounting for 557,213,447 people in 2020 and 561 RT facilities. Approximately 1,065,684 new cancer cases were diagnosed, and a mean density of 768,469 (standard deviation ±392,778) people per available unit was found. By projecting the currently available treatment fractions to determine those required in 2030, it was found that 62.3% and 130.8% increases in external beam RT and brachytherapy units are needed from the baseline, respectively. An overall regional investment of approximately United States (US) $349,650,480 in 2020 would have covered the existing demand. An investment of US $872,889,949 will be necessary by 2030, with the expectation of a 2-year posttreatment gross return on investment of more than US $2.1 billion from patients treated in 2030 only. Conclusions: Investment in RT services is lagging in Latin America in terms of the population's needs. An accelerated outlay could save additional lives during the next decade, create a self-sustaining system, and reduce region-wide inequities in cancer care access. Cash flow analyses are warranted to tailor precise national-level intervention strategies.